CREATIVE ECONOMIES IN THE DIGITAL AGE: ENTREPRENEURIAL MANAGEMENT FOR SOCIAL SUSTAINABILITY - Murdana, I Made; Chan, Rachel; Koh, Megan (Yayasan Adra Karima Hubbi, 2026)
The rapid evolution of digital technologies has significantly transformed creative economies, shifting the focus of entrepreneurship from traditional models to digital platforms. Despite the growing recognition of social sustainability, many creative entrepreneurs still prioritize economic goals, leaving social responsibility as a secondary concern. This study explores how entrepreneurial management practices can integrate social sustainability in creative industries, specifically within the context of the digital age. The research aims to investigate the strategies entrepreneurs employ to balance profit generation with social responsibility, focusing on the role of digital tools in promoting sustainable practices. A mixed-methods approach was used, combining qualitative interviews with 50 entrepreneurs and a survey of 200 participants. The findings indicate that while digital platforms enable creative entrepreneurs to engage in social sustainability, a significant gap exists between the recognition of its importance and its implementation. Entrepreneurs who prioritize sustainability often face challenges, including limited resources and a lack of awareness about effective strategies. This study contributes to the literature by offering a conceptual framework for integrating social sustainability into entrepreneurial management within creative economies. It highlights the need for targeted policies and support mechanisms to foster sustainable practices in the sector. The research underscores the potential for digital tools to drive both economic success and social responsibility in creative industries.